Hematocrit and total protein elimination as quality control parameters of cell salvage - Dörffel Debora; Klotz Edda; Wagner Patrick; Ehrig Karsten; Pretzel Karin; Hanisch Falko; Pruß Axel (The Journal of ExtraCorporeal Technology)
Background: The use of cell salvage reduces homologous blood transfusions during operations and avoids associated complications. Therefore, autotransfusion is an integral part of Patient Blood Management (PBM). The quality control of cell salvage in Germany is performed by checking the target values of a hematocrit in the autotransfusion blood (target: over 50%) and a total protein elimination (target: over 90%). The aim of this study was to identify intraoperative circumstances leading to deviations from the target values. Methods: This retrospective data analysis includes the use of the cell saver at the Charité – Universitätsmedizin Berlin, Campus Charité Mitte and Campus Benjamin Franklin from 01.01.2019 to 29.03.2022, in which autotransfusion occurred. In addition to the hematocrit and total protein elimination, the age and gender of the patients, as well as the surgical diagnosis, were included to investigate possible factors influencing compliance with the target values. The data were statistically analyzed using SPSS. Results: A total patient collective of 238 cell salvage applications (154 men, 84 women) was examined. The target values for quality control were achieved on average. The target value for hematocrit was not achieved in about 22% and for total protein elimination in about 8% of cell salvage applications. The age and gender of the patient, as well as the surgical diagnosis, had very little to no influence on compliance with the target values. The target values were not met primarily when the emergency option of the cell saver was used, when the collection volume was too low or when the collection volume was heavily diluted with rinsing fluid. Conclusion: The target values for quality control were achieved in most of the cell salvage applications examined and are suitable for ensuring the quality of autotransfusion. Special clinical circumstances may lead to the treating anesthetist having to accept deviating collection volumes or washing processes.